1996
DOI: 10.1002/(sici)1098-1101(1996)11:4<185::aid-jca3>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Successful collection and transplantation of peripheral blood stem cells in cancer patients using large-volume leukaphereses

Abstract: It was the aim of our study to determine the collection efficiency and yield of CD34+ cells in 88 cancer patients (pts, 44 males/44 females) who underwent 154 large‐volume leukaphereses (LV‐LPs). The diagnoses were as follows: 18 patients had Non‐Hodgkin's lymphoma, 9 Hodgkin's disease, 24 multiple myeloma, 6 acute leukemia, 27 breast cancer, and 4 patients had solid tumors of different types. During the course of LV‐LPs, 20 liters (l) of blood were processed at a median flow‐rate of 85 ml/min (CS 3000 Baxter)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 23 publications
2
27
1
Order By: Relevance
“…The ability to collect with a single large-volume leukapheresis enough PBPC for hematopoietic rescue after high-dose chemotherapy has been reported in 70 to 92% of patients with various hematologic or solid organ malignancies [14,19]. When standard volume leukaphereses are performed the proportion of patients presenting with single harvests of 2.5 × 10 6 or more, CD34+ cells/kg is significantly lower [14].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The ability to collect with a single large-volume leukapheresis enough PBPC for hematopoietic rescue after high-dose chemotherapy has been reported in 70 to 92% of patients with various hematologic or solid organ malignancies [14,19]. When standard volume leukaphereses are performed the proportion of patients presenting with single harvests of 2.5 × 10 6 or more, CD34+ cells/kg is significantly lower [14].…”
Section: Discussionmentioning
confidence: 97%
“…Fifteen patients required admission to the hospital for complications related to mobilization but there was no procedure-related death. Recent data have shown that adequate progenitors to sustain long-term hematopoiesis can be collected with a single leukapheresis [4][5][6]14,15]. In an attempt to limit the number of aphereses, which is a time-consuming and a cost-limiting factor, we developed a VLVL programme by processing up to 10× the patient blood volume.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[169][170][171][172][173][174][175][176][177][178] Typically, the quantity of blood processed is 6 or more times the patient's blood volume, often 25 to 36 L of blood. Thus, for a consistent quantity of blood processed through the machine, the quantity of CD34+ cells collected is directly related to the number present in the peripheral blood.…”
Section: Large-volume Leukapheresismentioning
confidence: 99%